Protein–Protein Interactions between Sucrose Transporters of Different Affinities Colocalized in the Same Enucleate Sieve Element - Reinders, Anke (American Society of Plant Biologists, 2002)
Suc represents the major transport form for carbohydrates in plants. Suc is loaded actively against a concentration gradient into sieve elements, which constitute the conduit for assimilate export out of leaves. Three members of the Suc transporter family with different properties were identified: SUT1, a high-affinity Suc proton cotransporter; SUT4, a low-affinity transporter; and SUT2, which in yeast is only weakly active and shows features similar to those of the yeast sugar sensors RGT2 and SNF3. Immunolocalization demonstrated that all three SUT proteins are localized in the same enucleate sieve element. Thus, the potential of Suc transporters to form homooligomers was tested by the yeast-based split-ubiquitin system. The results show that both SUT1 and SUT2 have the potential to form homooligomers. Moreover, all three Suc transporters have the potential to interact with each other. As controls, a potassium channel and a monosaccharide transporter, expressed in the plasma membrane, did not interact with the SUTs. The in vivo interaction between the functionally different Suc transporters indicates that the membrane proteins are capable of forming oligomeric structures that, like mammalian Glc transporter complexes, might be of functional significance for the regulation of transport.